121k views
4 votes
Solve for x, 12y+6=6(y+1)

User Adamgy
by
5.3k points

1 Answer

5 votes

For this case we must solve the following equation:


12y + 6 = 6 (y + 1)

We apply distributive property on the right side of the equation:


12y + 6 = 6y + 6

We subtract 6y on both sides of the equation:


12y-6y + 6 = 6\\6y + 6 = 6

We subtract 6 from both sides of the equation:


6y = 6-6\\6y = 0

Dividing by 6 on both sides of the equation:


y = 0

So, the result is
y = 0

Answer:


y = 0

User Timger
by
5.5k points